Fire with fire - Fox, Candice (Forge, Tor Publishing Group, 2023)
"A pair of desperate parents. A man on the run. A rookie cop. Four people with everything on the line. What will be left in the ashes of the next 24 hours? Following their daughter's mysterious disappearance, Ryan and Elsie Delaney have taken the LAPD forensic lab hostage, and have given law enforcement an ultimatum: Find their daughter, Tilly, or they will destroy all the evidence they can find to other cold cases. Detective Charlie Hoskins has been undercover in a deadly motorcycle gang for five years. With his cover blown, he has no choice but to find Tilly himself, or lose everything he's worked for as the lab burns. Lynette Lamb was a police officer -- until yesterday, when she was fired before her first beat. Figuring out what happened to Tilly is her one and only chance at rejoining the career she's prepared her whole life for. Hoskins and Lamb will have to team up to solve this cold case, and will have to move fast -- before the situation explodes"--